Flexible Process Design for Urban Rail Transit Vehicle Overhaul - Zailing ZHOU; Zhiyuan LIU; Huibo GONG; Gehui LIU; Yaping WANG (Chengshi guidao jiaotong yanjiu, 2024)
[Objective] Overhaul operations for urban rail transit vehicles pose challenges and bottlenecks in the organization of maintenance work. Currently, there is a lack of systematic exploration of the overhaul contents and process design tailored for maintenance. [Method] Analyzing and refining the process design for the advanced overhaul schedule of urban rail transit vehicles is essential to improving the rationality of maintenance work arrangement, and effectively address the increased maintenance work demands resulting from the expansion of line network mileage and passenger flow volume. Based on existing research achievements regarding maintenance facility layout and maintenance task sequence optimization, the current urban rail transit vehicle overhaul situation is analyzed. Features such as shift repairs between lines, concentrated component-specific repairs, and diverse maintenance strategies in the overhaul operations are summarized. Subsequently, the process characteristics of the overhaul are outlined from the perspectives of process flow, maintenance strategies, and allocation of maintenance resources. Furthermore, a flexible process for overhaul is proposed, including the introduction of parallel operations in the process flow, adjustment of maintenance strategies based on the operational capacity of the maintenance line, and the separation of maintenance equipment and personnel in the allocation of maintenance resources. A computational example analysis is carried out based on the actual overhaul process of a 6-car formation urban rail transit train. [Result & Conclusion] Under a fixed process flow, the overhaul time required for synchronous maintenance strategy is 25 days. By applying flexible process, the required maintenance time is reduced to only 17.5 days, resulting in a 7.5-day reduction in maintenance time compared to the fixed process. The reduction in maintenance time stems from the introduction of parallel operations and the avoidance of executing synchronous overhaul strategy for the entire vehicle when the maintenance facility capacity is insufficient. The computational example results indicate that applying flexible process can effectively shorten the overhaul time of trains, thereby enhancing the maintenance efficiency of urban rail transit vehicles.